6-Ketocholestanol suppresses lipid accumulation by decreasing FASN gene expression through SREBP-dependent regulation in HepG2 cells - Shirouchi, Bungo (Cytotechnology, 2020)
Nuclear receptors, such as liver X receptors (LXRs) and sterol regulatory element-binding proteins (SREBPs), are key regulators of lipogenic genes, including fatty acid synthase (FASN). It has been reported that several oxycholesterols (OCs) act as LXR ligands; however, it is unclear whether all OC molecular species act as ligands. We previously demonstrated that the absorption rate of dietary 6-ketocholestanol (6-keto), an oxycholesterol, is the highest of all the OCs using thoracic lymph duct-cannulated rats. However, limited information is available about the physiological significance of 6-keto. In this study, we investigated whether treatment with 6-keto increases intracellular triacylglycerol (TAG) levels through up-regulation of lipogenic gene expression in HepG2 cells. 6-Keto treatment significantly reduced intracellular TAG levels through down-regulation of lipogenic genes including FASN. Although 6-keto significantly suppressed FASN gene promoter activities, the action was completely diminished when mutations were present in the SREBP promoter site. TO901317 (TO) significantly increased FASN gene promoter activities, whereas simultaneous treatment with TO and 6-keto significantly reduced this activity. We also compared the effects of several OCs that are oxidized at the carbon-6 and -7 in the B-ring of cholesterol on FASN gene promoter activities. Similar to 6-keto, 6α-OH and 6β-OH significantly reduced the activity of the FASN gene promoter, which suggests that oxidation of carbon-6 in the B-ring may play an important role in the reduction of FASN expression. Our results indicate that 6-keto suppresses lipid accumulation by decreasing FASN gene expression through SREBP-dependent regulation in HepG2 cells. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s10616-019-00368-5) contains supplementary material, which is available to authorized users.